Harvesting Systems, Soil Cultivation, and Nitrogen Rate Associated with Sugarcane Yield - Quassi de Castro, Sérgio Gustavo; Graziano Magalhães, Paulo Sérgio; Coutinho Junqueira Franco, Henrique; Mutton, Miguel Ângelo [UNESP] (Springer Nature, 2018)
The adoption of mechanical harvesting of green cane gives rise to concerns as to whether systems developed under burnt cane harvesting are applicable to a green cane harvesting system. In particular, tillage, which is an integral part of the burnt cane system, may no longer be necessary, and the nitrogen fertilizer rates required may need to be replaced due to the large amounts of organic matter being returned to the soil after green cane harvesting. Mechanical harvesting is relatively new in Brazil and little is known about its effect on other sugarcane production strategies. This work aimed to evaluate sugarcane performance under not only different harvesting and cultivation systems, but also different nitrogen fertilizer rates over a 3-year period. The experimental design was a split plot with harvesting systems (burnt vs. green) as main plots, cultivation (interrow vs. no cultivation) as sub plots, and nitrogen rates as sub-sub plots. The harvesting systems produced similar sugarcane yields throughout the experimental period, which demonstrates that the harvest systems do not influence sugarcane yield. Mechanical tillage practices in interrow after harvesting had no impact on stalk yield or sugar quality, indicating no necessity for this operation in the following crop. Ratoon nitrogen fertilization promoted an increase of stalk and sugar yield, with highest yields obtained at the rate of 130 kg ha−1 N. However, there was no interaction between harvesting system and nitrogen rate.
Keywords: Green cane trash blanket; Nitrogen fertilizer; Saccharum spp; Sugar production